The Perception of Work-Related Stress Indicators and the Relative Importance of Job Demand Stressors Among Construction Professionals in Malaysia - Abas, Nor Haslinda (International Journal of Sustainable Construction Engineering and Technology, 2021)
In several countries in the world, work-related stresses faced among the professionals in the construction industry came together with the significantly unidentified symptoms and factors. Occupational stress could negatively affect the mental, physical, and behavior of an individual. The factors of work-related stress commonly caused by high job demand with low job control and support, the poor physical environment of an organization, discrimination from employers and employees, and conflict outside of work. The study of occupational stress had been researched by many researchers, but the study of occupational stress particularly among construction professionals is still lacking in Malaysia. Therefore, this study aims to investigate the occupational stress levels that are focusing on professionals who work in the construction industry in Malaysia. A multi-sectional questionnaire is developed to identify the level of work stress, factors that contribute to work stress, and the effects on professionals in the construction industries. The analysis shows that the professionals faced a controlled level of stress on physical, mental, and emotional states. Furthermore, some of the few top job demand stressors are obtained, which are critical cost constraints, the need for interpersonal skills, and the high frequency of reporting demand. Although the professionals’ stress levels are in the non-very-critical levels, there are still cases that fall into the critical level. This study has investigated the causes of occupational stress among professionals and how they affected their mental, emotional, and physical state. Moreover, this study has identified the job demand factors that contributed to the stress level of the professionals. At the same time, filling the gaps of previous studies related to the work-stress level on the professionals in the Malaysian construction industry.